An Empirical Study on Announcement Effect of Right Issue Ex-Date - Maulani, Denia; Istirhamiyah, Siti; Suharti, Titing (Universitas Ibn Khladun Bogor, 2024)
This research aims to examine how the market reacts regarding the announcement of the rights issue and how the market reacts at the ex date. The sampling technique is purposive sampling, namely companies that carry out rights issues and are active banking on the Indonesian Stock Exchange. Testing period 2015 to 2021. The technique used is multiple linear regression test and paired sample T test. The total number of companies is 27 issuers with research results showing that the announcement of a rights issue has an effect on changes in share prices where the p-value of the pair sample t-test is less than 0.05. Meanwhile, testing the market reaction regarding the ex date shows that there was a significant decline in stock prices so that the market reacted negatively with a p-value of less than 0.05 and there was a significant change in stock trading volume during the ex date condition with a p-value of less than 0.05.